Characterization of Copper Adsorption onto an Alginate Encapsulated Magnetic Sorbent by a Combined FT-IR, XPS, and Mathematical Modeling Study - Soh-Fong, Lim; Yu-Ming, Zheng; Shuai-Wen, Zou; Chen, J.Paul (American Chemical Society, 2008)
Copper adsorption onto calcium alginate encapsulated magnetic sorbent is studied in this paper. The objective of this study was to qualitatively and quantitatively elucidate the copper binding onto the sorbent. The adsorption increases from around 0 to almost 100% as the initial pH is increased from 2 to 5. A maximum adsorption capacity of 0.99 mmol g−1 is achieved. The FT-IR and XPS studies show that the C—O in carboxyl group of alginate directly attaches to the copper ion that leads to most of the adsorption. A mathematical model is developed, and it includes ion exchange between the calcium and the copper, coordination reaction between the functional group and the copper, as well as surface complex formation between the iron oxide and the copper. The model is capable of describing and predicting effects of various key operational parameters on the adsorption process, such as initial pH, metal concentration, and dosage of sorbent.